Poetinio diskurso kalbinių raiškos priemonių adekvatumas lietuvių ir anglų kalbose - Buitkienė, Janina (Kalbotyra, 2000)
This article tries to throw some light upon the differences in the structuring of texts in the process of translation. These differences are connected with certain variations at the surface level of the text (text cohesion) while it is assumed that the deep structure of the original (text coherence) has to be preserved while translating. A Lithuanian poetic text and its translation into English were analyzed. The obtained data show that the translator allowed for certain modifications on the surface level of the discourse which manifest themselves most clearly in the omissions, additions and alternations. The data also prove that the more culture-bound a text is, the more scope there may be for modification.